Consensus recommendations for diagnosis, management and treatment of Fabry disease in paediatric patients. Issue 2 (6th June 2019) - Germain, Dominique P.; Fouilhoux, Alain; Decramer, Stéphane; Tardieu, Marine; Pillet, Pascal; Fila, Marc; Rivera, Serge; Deschênes, Georges; Lacombe, Didier
Abstract: Fabry disease (FD), a rare X‐linked disease, can be treated with bi‐monthly infusion of enzyme replacement therapy (ERT) to replace deficient α‐galactosidase A (AGAL‐A). ERT reduces symptoms, improves quality of life (QoL), and improves clinical signs and biochemical markers. ERT initiation in childhood could slow or stop progressive organ damage. Preventative treatment of FD from childhood is thought to avoid organ damage in later life, prompting a French expert working group to collaborate and produce recommendations for treating and monitoring children with FD. Organ involvement should be assessed by age 5 for asymptomatic boys (age 12‐15 for asymptomatic girls), and immediately for children diagnosed via symptoms. The renal, cardiac, nervous and gastrointestinal systems should be assessed, as well as bone, skin, eyes, hearing, and QoL. The plasma biomarker globotriaosylsphingosine is also useful. ERT should be considered for symptomatic boys and girls with neuropathic pain, pathological albuminuria (≥3 mg/mmol creatinine), severe GI involvement and abdominal pain or cardiac involvement. ERT should be considered for asymptomatic boys from the age of 7. Organ involvement should be treated as needed. Early diagnosis and management of FD represents a promising strategy to reduce organ damage, morbidity and premature mortality in adulthood. Abstract :